Genetic structure of Eurasian beaver in Romania: insights after two decades from the reintroduction - Fedorca, Ancuta; Ciocirlan, Elena; Pasca, Claudiu; Fedorca, Mihai; Gridan, Alexandru; Ionescu, Georgeta (Springer Science and Business Media LLC, 2021)
Once exploited for fur, meat, and extracting the yellowish exudate called castoreum, the Eurasian beaver disappeared from Romania during the eighteenth century. After, the reintroductions carried out two decades ago are currently thriving in the Danube River basin. Using nine nSSR markers, we analysed samples from 98 individuals, and we found no genetic substructure, suggesting high dispersal and gene flow capabilities. The stepwise mutation model (SMM) indicated the existence of a recent genetic bottleneck, though the Eurasian beaver retains high levels of genetic diversity and population growth facilitated variation in nSSR loci. A fine-scale spatial correlation in females was detected, contrasting with males’ dispersal on longer distances. While the movement and establishment of individuals’ new territories were made under natural predation pressure, the mix following natural expansion improved the fitness and could contribute to a higher genetic diversity than the source population. With any reintroduction, a focus on capturing individuals from various geographic origins, as well as securing many and suitable founding individuals (adults, subadults, and juveniles) with mixed origins, could secure the post-genetic bottleneck recovery and higher genetic diversity. Beyond this conservation success, future management strategies should consider building a National Action Plan (NAP) for the species, including a permanent genetic monitoring programme for Eurasian beaver.